Maturation and postharvest quality of 'Laetitia'plums with preharvest treatment of AVG and GA3 Maturação e qualidade pós-colheita de ameixas 'Laetitia' com a aplicação pré-colheita de AVG e GA3 - Steffens, Cristiano Andre (2011)
The objective of this study was to evaluate the effects of preharvest spraying of Japanese plum trees (Prunus salicina, cv. Laetitia) with aminoethoxyvinilglycine [AVG; at 0, 90, and 125 mg L-1] and giberellic acid [GA3; at 0 and 100 mg L-1] on maturation and fruit quality after cold storage. The experiment followed a randomized block design, with six treatments (three doses of AVG x two doses of GA3) and four replicates. The sprayings with GA3 and AVG were performed at 28 and seven days before first fruit harvesting, respectively. Experiment was carried out during the years of 2007 and 2009. Fruits were harvested 3 times, being 01/11/2007, 01/17/2007 and 01/25/2007 (commercial harvest) 2007, and 01/15/2009, 01/22/2009 (commercial harvest) e 01/29/2009, in 2009. At 2007, fruits of the last harvest were stored in commercial cold storage during 22 days (0.5°C/92% RH), followed by five days of shelf life (23°C/60% RH). Delays in harvesting induces of fruit ripening, however preharvest treatment only with AVG (125 mg L-1) singly or GA3, followed or not by the application of AVG, delay fruit ripening of 'Laetitia' plums plant. Preharvest spraying of 'Laetitia' plum trees with GA3 followed by the application of AVG preserves the consistence of the pulp fruit after cold storage.